2020
DOI: 10.1136/tobaccocontrol-2020-055985
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, trial and use of heated tobacco products among adult cigarette smokers and e-cigarette users: findings from the 2018 ITC Four Country Smoking and Vaping Survey

Abstract: ObjectiveTo evaluate heated tobacco product (HTP) awareness, trial and current use among adult cigarette smokers and vaping product users in four countries with varying regulations governing HTP sales.DesignData came from Wave 2 of the ITC Four Country Smoking and Vaping Survey, collected from February to July 2018. Respondents were current and former smokers and/or users of vaping products (18 years or older) from Canada (CA; n=3778), England (EN; n=4848), the USA (US; n=2846) and Australia (AU; n=1515). At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Overall, current use appears not to have increased (for example 2.0% among current smokers in 2017 compared with 1.7% among exclusive smokers in this survey). Prevalence among smokers, recent ex-smokers and vapers in the present survey was consistent with previous surveys [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, current use appears not to have increased (for example 2.0% among current smokers in 2017 compared with 1.7% among exclusive smokers in this survey). Prevalence among smokers, recent ex-smokers and vapers in the present survey was consistent with previous surveys [29].…”
Section: Discussionsupporting
confidence: 92%
“…If these products help smokers to stop and/or are significantly less harmful, then more needs to be done to increase their use among exclusive smokers. Regulatory restrictions may then need to be reconsidered, although a crosscountry study only found small differences between countries varying even on legal availability [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current HTP use rose in Japan from 0.2% in 2015 to 10%-15% in 2019, [30][31][32] and 4.4% of adults in Korea currently use an HTP. 33 Prevalence has been lower across European countries (eg, 0.1% current users in 2016-2018), 34 but seems to be increasing in select markets (eg, 1.1%-Italy 2019 35 ; 1.2%-England 36 ).…”
Section: Heated Tobacco Productsmentioning
confidence: 99%
“…This assertion requires further elucidation, due to a paucity of studies on long-term health effects of HNBC and the increasing use of HNBC, especially among current TCC smokers. 1 Therefore, the two reports in this issue of Thorax, by Loffredo et al and Kanai et al, 2 3 two research groups unaffiliated with tobacco industry, are timely, providing new insights into the harmful impact of chronic HNBC use on endothelial function and questioning its usefulness for tobacco cessation, respectively.…”
mentioning
confidence: 99%